2012
DOI: 10.1016/j.compedu.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A conversational intelligent tutoring system to automatically predict learning styles

Abstract: This paper proposes a generic methodology and architecture for developing a novel conversational intelligent tutoring system (CITS) called Oscar that leads a tutoring conversation and dynamically predicts and adapts to a student's learning style. Oscar aims to mimic a human tutor by implicitly modelling the learning style during tutoring, and personalising the tutorial to boost confidence and improve the effectiveness of the learning experience. Learners can intuitively explore and discuss topics in natural la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(130 citation statements)
references
References 23 publications
0
93
0
1
Order By: Relevance
“…The factor of Learning Data is retrieved in the SCI. Some researchers indicated that smart classroom can give adaptive learning support to the student by detecting, recording, and analyzing the students' entire learning statuses (Dogan and Camurcu 2007;Zhang et al 2009;Latham et al 2012). Students' learning data is the basis for constructing learning model and giving the individualized learning diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The factor of Learning Data is retrieved in the SCI. Some researchers indicated that smart classroom can give adaptive learning support to the student by detecting, recording, and analyzing the students' entire learning statuses (Dogan and Camurcu 2007;Zhang et al 2009;Latham et al 2012). Students' learning data is the basis for constructing learning model and giving the individualized learning diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, this learning style model was used because learning objects were presented to students in an online environment. Felder and Silverman's learning style model [13] determines the learning style of an individual by scoring the nature and power of his/her learning preferences in four dimensions (perception, input, processing and understanding) [30]. The perception dimension describes the relationship of a student with the information type he/she prefers perceiving; the processing dimension describes the conversion pattern of the perceived information to understanding; the input dimension describes the preference pattern of the students to receive external information; and the understanding dimension describes the student' understanding processes [15].…”
Section: Learning Stylesmentioning
confidence: 99%
“…They find the Markov based approach leads to more fine-tuned results than the Genetic Algorithm. Latham, Crockett, McLean, and Edmonds (2012) predict students' learning style through natural language dialogue. In this respect, they analyze the learning style models for language traits and conversational structure and adapt the generic logic rules to predict learning styles.…”
Section: Learning Style Modelingmentioning
confidence: 99%